Mitigasi Bencana Berbasis Pelestarian Kearifan Lokal Kentongan - Triyadi Haryanto; Suwarsito Suwarsito; Esti Sarjanti (UM Purwokerto Press, 2022)
Indonesia is one of the countries prone to natural disasters. This condition is inseparable from the geological location of Indonesia, which is at the confluence of two large plates of Eurasian and Indoaustralia. The result of the meeting. As a country with a high disaster risk, the Indonesian people must have the readiness and ability to deal with such disasters. One of the most important aspects of disaster risk reduction at the local level is the social capital that can be obtained from the cultural diversity of the Indonesian people through local wisdom. Local knowledge or can be referred to as local wisdom can be used by the community as one of the efforts in Disaster Risk Reduction. Local wisdom plays an important role in mobilizing community efforts to increase community resilience in dealing with disasters. The spirit of self-help community, mutual cooperation in preserving nature is one of the main assets in dealing with disaster risk. Local wisdom is an asset that can be managed in building a community-based disaster management system, especially at the disaster mitigation stage. This study is a literature study. This study was conducted by analyzing the literature related to disaster mitigation with local wisdom that is still being implemented in the community. Collecting data by reading, recording and processing data to understand the phenomena that occur. Concept analysis is carried out by synthesizing several articles to find the existence of local wisdom in disaster mitigation. The study aims to revive local wisdom of kentongan in the community in disaster mitigation efforts so as to reduce victims. Although the kentongan is categorized as a traditional communication tool like other things such as smoke, pigeons, and so on, it turns out that the kentongan is more able to survive and compete with the existence of modern communication tools that are far more advanced. This indicates that the kentongan still has